Administrative and legal mechanisms of management of medical support of the armed forces: historical experience and current trends - Грищук, Б. А. (Київський національний університет імені Тараса Шевченка, 2025)
The article provides a comprehensive analysis of the administrative and legal mechanisms governing medical support of the Armed Forces of Ukraine in the context of historical development and the contemporary challenges of the full-scale war. It is emphasized that effective medical support is a critical determinant of military combat capability, while hostilities have revealed both achievements and systemic problems in the areas of regulatory framework and managerial coordination. Considerable attention is paid to the evolution of the military medical system and the formation of its legal and regulatory basis. The study traces the path from fragmented attempts to organize sanitary administration during the period of the Ukrainian liberation struggles and the Soviet departmental model to the establishment in 2020 of a separate branch of forces – the Medical Forces of the Armed Forces of Ukraine. This institutional transformation changed the status of medical support by elevating it to the level of strategic planning. The regulatory framework rests on the Constitution, the Laws of Ukraine “On the Defense of Ukraine” and “On the Armed Forces of Ukraine,” as well as specialized legislation, including Law No. 10343, which initiated the implementation of NATO standards at the level of clinical protocols and requirements for medical supplies. An important role is played by the Doctrine on Medical Support of the Defense Forces, which, although not a law, serves as a doctrinal guideline for harmonizing the national system with Alliance principles. The functioning of the administrative and legal mechanism is described in detail, covering governance actors, legal instruments, and organizational procedures. Key actors include the Ministry of Defense, which shapes policy through the relevant department, and the Medical Forces Command, which ensures practical implementation of medical support. The procedural component includes algorithms for military medical examination, evacuation, and provision of care at different levels. Particular emphasis is placed on interagency cooperation and financial-legal mechanisms for settlements between military and civilian healthcare institutions, which underpin the integrated use of resources amid mass sanitary losses. The role of oversight – departmental, parliamentary, and public – is also highlighted as an instrument for ensuring legality and protecting the rights of servicemembers. Five major trends in the development of contemporary management mechanisms are identified: adaptation to high-intensity warfare, systematic implementation of NATO standards, development of a unified medical space in Ukraine, increased attention to rehabilitation and mental health, and digitalization of processes. Challenges related to the fragmented nature of the regulatory framework and insufficient funding are noted. As promising directions for improvement, the article proposes systematization of legislation (potential codification), deeper institutional consolidation, development of the eHealth system within the military sector, and ensuring transparency of managerial processes. It is demonstrated that the current stage constitutes a historical window of opportunity to build an effective, NATO-interoperable, and human-centered system of military medicine.

У статті здійснено комплексний аналіз адміністративно-правових механізмів управління медичним забезпеченням Збройних Сил України в контексті історичного розвитку та сучасних викликів повномасштабної війни. Зазначено, що ефективність медичного забезпечення є критичним чинником боєздатності війська, а бойові дії виявили як досягнення, так і системні проблеми у сфері нормативного регулювання та управлінської узгодженості. Значну увагу приділено еволюції системи військової медицини та формуванню її нормативно-правової бази. Простежено шлях від фрагментарних спроб організації санітарних управ часів визвольних змагань та радянської відомчої моделі до створення у 2020 році окремого роду сил – Медичних сил Збройних Сил України. Це інституційне перетворення змінило статус медичного забезпечення, вивівши його на рівень стратегічного планування. Нормативний каркас системи спирається на Конституцію, закони «Про оборону України», «Про Збройні Сили України» та спеціалізоване законодавство, зокрема закон №10343, який запустив процес імплементації стандартів НАТО на рівні клінічних протоколів та вимог до медичних засобів. Важливу роль відіграє Доктрина з медичного забезпечення сил оборони, яка, хоч і не є законом, виконує функцію доктринального орієнтира для гармонізації національної системи з принципами Альянсу. Детально охарактеризовано функціонування адміністративно-правового механізму, який охоплює суб’єктів управління, правові інструменти та організаційні процедури. Ключовими суб’єктами виступають Міністерство оборони, що формує політику через профільний департамент, та Командування Медичних сил, яке забезпечує практичну реалізацію медичного забезпечення. Процедурний складник включає алгоритми військово-лікарської експертизи, евакуації та надання допомоги на різних рівнях. Окремий акцент зроблено на важливості міжвідомчої взаємодії та фінансово-правових механізмах розрахунків між військовими та цивільними закладами охорони здоров’я, що є основою для інтегрованого використання ресурсів в умовах масових санітарних втрат. Також підкреслено роль контролю – відомчого, парламентського та громадського – як інструменту забезпечення законності та захисту прав військовослужбовців. Виокремлено п’ять основних тенденцій розвитку сучасних механізмів управління: адаптація до умов війни високої інтенсивності, системна імплементація стандартів НАТО, розбудова єдиного медичного простору України, посилення уваги до реабілітації та ментального здоров’я, а також цифровізація процесів. Констатовано виклики, пов’язані з фрагментарністю нормативної бази та недостатнім фінансуванням. Як перспективні напрями вдосконалення механізму пропонуються систематизація законодавства (потенційна кодифікація), поглиблення інституційної консолідації, розвиток електронної системи охорони здоров’я (eHealth) у військовій сфері та забезпечення прозорості управлінських процесів. Доведено, що нинішній етап є історичним вікном можливостей для створення ефективної, сумісної з НАТО та людиноцентричної системи військової медицини.
Адміністративно-правові механізми управління медичним забезпеченням збройних сил: історичний досвід та сучасні тенденції
Keywords: administrative and legal mechanisms; medical support; Armed Forces of Ukraine; military medicine; Medical Forces of the Armed Forces of Ukraine; legal and regulatory framework; NATO standards; military medical examination; medical evacuation; interagency cooperation; doctrinal documents; medical protocols; digitalization; rehabilitation; national security.; адміністративно-правові механізми; медичне забезпечення; Збройні Сили України; військова медицина; Медичні сили ЗСУ; нормативно-правове регулювання; стандарти НАТО; військово-лікарська експертиза; медична евакуація; міжвідомча взаємодія; доктринальні документи; медичні протоколи; цифровізація; реабілітація; національна безпека.